CAPITAL EXPENDITURE, RISIKO SISTEMATIS, STRUKTUR MODAL DAN TINGKAT KEMAMPULABAAN TERHADAP NILAI PERUSAHAAN - Wemer R. Murhadi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2008)
This article aims to study capital expenditure, especially on intangible asset. Intangible asset is an asset, which can provide long-term competitive advantage that can improve value of the firm. This article relates capital expenditure, systematic risk, capital structure, profitability and value of the firm in one recursive model. This research use quantitative approach by using method of path analysis. This research uses sample in the natural resource sector for period 2006-2007, which listed on PT Indonesian Stock Exchange. Sample Final, which utilized in this research, is equal to 40-year observation. Research finding indicate that only capital structure and profitability that impact to value of the firm. Meanwhile, intangible asset proxies by research and development cannot influence profitability and value of the firm. Finally, systematic risk does not have significant influence to the value of the firm.